A notion of enterprise risk management enhancing strategies and wellbeing programs - Majumder, Soumi (Emerald Publishing Limited, 2024)
Soumi Majumder and Nilanjan Dey address the unique challenges posed by Industry 4.0, exploring the intersection of risks and cultural shifts within the business landscape. Key topics include the transformative potential of machine learning; big data; and IoT in the domain of enterprise risk management